Pattern of malignancy in clinically solitary thyroid nodule - Khan, SA; Gafur, MA; Khan, MK; Karim, MR; Mohiuddin, M; Islam, MS (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):1-7. The abstract of this article is available on the PubMed website.